Reindeer Returning from Combat:War Stories among the Nenets of European Russia - Dudeck, Stephan Johannes (Arctic Anthropology, 2018)
The following paper sheds new light on the Second World War oral history of the Nenets—indigenous people living in the northwestern part of the Russian Arctic. The participation of Nenets reindeer herders is commemorated and celebrated as part of the antifascist heroism of the Soviet people in the public historical discourse. Parts of the personal life stories Nenets elders shared in this research show striking differences to the public narratives of war. The paper analyzes the research setting as part of an oral history conducted with anthropological methods in order to learn about the Nenets historical experience as well as the Nenets ways of telling stories. The oralhistory interview is perceived as a performance and an emergent dialogic relationship involving the social relations of the narrator, the research setting, as well as the relation of the storyteller with different audiences.